INTEGRATION OF THE PROJECT-BASED LEARNING (PJBL) MODEL SUPPORTED BY WORDWALL INTERACTIVE MEDIA IN ECONOMICS EDUCATION: A LITERATURE REVIEW - Julita, Epa; Armiati (JURNAL PENDIDIKAN GLASSER, 2025)
This study examines the integration of Project-Based Learning (PjBL) and Wordwall interactive media in economics education through a Systematic Literature Review (SLR) and bibliometric analysis of ten articles published between 2020 and 2025. The findings show that PjBL, when supported by Wordwall, enhances students’ understanding of economic concepts, learning motivation, engagement, creativity, and critical thinking. Wordwall functions not only as a digital assessment tool but also as a medium for reflection, reinforcement, and real-time feedback. Bibliometric mapping reveals that the keyword “technology” dominates the discourse, indicating a shift toward digital, participatory, and contextual learning strategies. The integration of PjBL and Wordwall emerges as a transformative approach in reshaping economics education to meet the demands of the digital era. This review also identifies implementation patterns and pedagogical considerations essential for maximizing the impact of this integration. The study contributes to the growing body of literature supporting interactive, student-centered learning and offers practical insights for educators and policymakers seeking to modernize economic instruction